A novel approach for haploid generation in Lolium. (5th May 2020) - Kindiger, Bryan
Abstract: Development of haploid and/or dihaploid methodologies for Lolium sp. is important to future improvement efforts as the genus includes the majority of the world's cool‐season annual and perennial turf and forage grass species. Microspore or anther culture haploid induction systems can result in the generation of either maternal or paternal haploids that can be effectively used to advance genetic gains through a breeding or selection program. The successful and traditional approach for the production of haploids and eventually dihaploids in Lolium sp. is most successful when microspore culture approaches are applied. Unfortunately, this approach is labor‐intensive, expensive and often restrictive to amendable genotypes. Within the Lolium ‐ Festuca genome complex, there is a need for modern breeding approaches that can facilitate the rapid development of haploids or dihaploids for the development of improved germplasm or cultivars. It has been suggested that an in vivo approach could facilitate further advances in Lolium sp. genetic studies, molecular breeding and superior cultivar development. The recent development of a two novel annual ryegrass ( Lolium perenne L. subsp. multiflorum (Lam.) Husnot [syn. L. multiflorum Lam.]) line that when hybridized to tall fescue ( Schedonorus arundinaceus (Schreb.) Dumort., nom. cons.) has been previously demonstrated. This research investigates and reports on the potential generation of haploids and/or dihaploids through this novel ryegrass when hybridized with L. multiflorum or L. perenne and production of the first invivo haploid/dihaploid Lolium sp. approach.